TRAINING AND DEVELOPMENT SUMBER DAYA INSANI PADA KSPPS-BMT AL-MAKMUR: STUDI ANALISIS MELALUI PENDEKATAN BENEFIT, OPPORTUNITIES, COST, RISK (BOCR) - Ghita Ramadhayanti; Rizal Rizal; Himyar Pasrizal; Nil Firdaus (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
This research was triggered by LKMS's concerns with inadequate training and development execution, a lack of SOPs, awareness of the significance of training and development, which is still not a unit in BMT. The regulatory environment maintains BMT in an unstable condition, affecting the caliber of the unqualified human resources. The purpose of this research was to use the Benefit, Opportunity, Cost, and Risk (BOCR) approach to identify the many types of insani human resource training and development challenges, as well as the core causes of those concerns. The research method employed in this study is field research using a qualitative approach. Interviews, questionnaires, and documentation were utilized to collect data. The Analytic Network Process (ANP) approach using Super Decision 2.10 Software was utilized to analyze the data in this study, the findings of this study indicate that the problem of human resource training and development at KSPPS-BMT Al-Makmur is that there is no assistance after the training is given, and the quality of human resources is not qualified in terms of Islamic economics, resulting in several problems between the suitability of theory and practice in the field. One of the causes of this occurrence is the usage of speakers who are simply academics and are therefore less professional. The Covid-19 epidemic has forced the Koperindag Office and other agencies to not carry out training and development adequately, and there is no formal SOP that governs the implementation of training and development for LKMS, particularly at KSPPS-BMT Al-Makmur. Furthermore, based on the results of a pairwise comparison of five respondents using the Analytic Network Process (ANP) method and the Super Decisions software version 2.10, the results of the analysis of priority aspects with the highest priority are opportunities, namely with a value of (0.296), followed by analysis of priority criteria of benefits with a value of (0.309), opportunity (0.321), cost (0.413), and risk (0.413). (0.46705). While the fulfillment of qualified human resources is the most essential priority of the plan, with a score of (0.268), with the degree of agreement of respondents (W: 0.148) or (14.8%). Based on the findings of the study, the Koperindag Office recommends that BMTs get additional internal training, that mentorship and post-training assessments be conducted, and that the Koperindag Office build a digital platform for reporting for all BMTs in Tanah Datar.